Interactive Media for Islamic Education Dolanan Bocah Pinter (DOLPIN) Based on Local Wisdom in Strengthening Pancasila Student Profile - Idammatussilmi Idammatussilmi; Eko Handoyo; Amin Yusuf (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study was to determine the improvement of the character profile of Pancasila students through Dolanan Bocah Pinter (DOLPIN) Interactive media for Islamic Education. The lack of interactive media innovation in strengthening the profile of Pancasila students is the background of this research. The method used in this research is research and development (R and D) with the ADDIE approach. Data collection techniques; observation, interviews, test questions and documentation. The data validity test uses validity and reliability with validity tests including material experts, media experts and linguists. The results of this study indicate that the development of DOLPIN interactive media based on local wisdom is effective in increasing the profile of Pancasila students seen from the results of the classical test of material achievement 87% and the results of the classical test of the character of the Pancasila student profile 88%. The increase in material achievement and character profile of Pancasila students through one group pre-test and post-test output t test results, obtained sig value = 0.000, which means smaller than α 0.05. Teacher response to DOLPIN interactive media received a percentage of 97.6% (very good), and student response was 90.4% (very good). The application of DOLPIN interactive media based on local wisdom can improve the Pancasila learner profile of students in grade IV SD.